A Comparative Study of Tracheal Diameter in Caucasian and Chinese Patients. Issue 6 (November 2016) - Tai, A.; Corke, C.; Joynt, G. M.; Griffith, J.; Lunn, D.; Tong, P. W. Y.
Ethnicity may be considered a factor when considering what size endotracheal tube to insert. In particular it has been suggested that Chinese patients have a smaller tracheal diameter, justifying the selection of smaller endotracheal tubes. We systematically evaluated transverse tracheal diameters in Chinese and Caucasian patients, utilising archived computer tomography images. A convenience sample of 100 Caucasian patients from Australia was compared with 100 Chinese patients from Hong Kong. Patients over 18 years of age who had undergone a computerised tomography scan of the neck and thorax, and also had accurate body height and weight recorded, were studied. The mean transverse diameter of the trachea measured at three levels was similar between the Chinese and Caucasian patients. At the narrowest measurement point, the immediate subcricoid transverse diameter, the unadjusted mean difference between male Chinese and Caucasian patients was small (1 mm, standard deviation 0.83 mm, P =0.01), and similarly small between female Chinese and Caucasian patients (1.5 mm, standard deviation 0.8 mm, P <0.01). Multivariate analysis demonstrated only a small influence related to ethnicity (12% relative contribution to the overall variance [R 2 ] of the model), but substantial influence of height (40%) and sex (41%). Our findings do not support the practice of routinely selecting a smaller endotracheal tube size for Chinese patients on the basis that there is a difference related to the Chinese ethnic phenotype. Considerations regarding choice of endotracheal tube size should rather focus on patient sex and height.